Current perspectives on delivery systems using extracellular vesicles in neurological disease - Tran, Phuong H.L.; Duan, Wei; Lee, Beom Jin; Tran, Thao T.D. (Current Pharmaceutical Design, 2020)
Extracellular vesicles have an excellent ability to transfer their contents to cells. Extracellular vesicles can also be engineered to deliver therapeutic molecules to target cells. Although a number of studies have exploited synthesized nanoparticles in the treatment of neurological disease in the past few years, extracellular vesicles have been investigated and shown tremendous promise for clinical applications because they are safe and have strong targeting specificity. Different types of extracellular vesicles have been studied and modified for delivering therapeutic factors in neurological disease, including extracellular vesicles loaded with natural therapeutic factors and therapeutic molecules. In this review, we discuss delivery systems using extracellular vesicles containing molecules of interest and then focus on main strategies used for EV loading and surface modification. Discussing these important issues will support and facilitate the design and development of promising techniques and products for neurological therapy.
Keywords: Drug Delivery Systems; Extracellular Vesicles; Humans; Nanoparticles; Nervous System Diseases; Delivery system; Extracellular vesicles; Loading; Neurological disease; Specificity; Therapeutic molecules